Makan Menurut Injil Markus dan Fenomena Food Waste serta Kelaparan di Indonesia - Milala, Raharja Sembiring; Sitanggang, Asigor Parongna (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2025)
AbstractThis article examines the act of eating as a routine occurrence. The evolution of society has altered the significance of food as an indicator of social status and prestige. This change in perception affects issues like food waste, hunger, malnutrition, and stunting. By analyzing the eating narratives in the Gospel of Mark through editorial criticism, we find that eating is connected to the principles of inclusivity and the readiness to share within the community of God’s followers. The article presents eating as an opportunity to extend and share God’s gracewith all individuals. This concept can offer fresh perspectives for faith communities in developing an ethical approach to food and supporting those in need. AbstrakArtikel ini mendiskusikan makan sebagai fenomena keseharian. Progresivitas zaman berimbas pada pemaknaan makan sebagai penanda kelas sosial dan prestige. Konsekuensi pergeseran makna ini berdampak pada food waste, kelaparan, gizi buruk, dan stunting. Penelusuran teks-teks makan dalam Injil Markus dengan menggunakan kritik redaksi menibakan kita pada kesimpulan bawa makan berelasi dengan nilai-nilai inklusivitas dan kesediaan berbagi dalam komunitas umat Allah. Artikel ini menawarkan makan sebagai ruang welcoming dan berbagi rahmat Allah pada semua orang. Gagasan ini dapat menjadi insight baru bagi komunitas orang percaya dalam membentuk sikap etis terhadap makanan dan saudara yang kekurangan.